Triphenylamine polyamide containing quinoxaline structure as well as preparation method and application of triphenylamine polyamide
By introducing quinoxaline structure and triphenylamine moieties into the polyamide, the problem of poor stability of polyamide in solution processing and electrochromic cyclic cyclic is solved, and high solubility, excellent electrochromic performance and long cycle stability are achieved.
Patent Information
- Application Number
- CN202411722671.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-04
AI Technical Summary
Polyamides have problems such as difficult to process solution, poor film formation effect, and poor electrochromic cycle stability.
By introducing quinoxaline structure and triphenylamine moieties, triphenylamine polyamides with propeller structure were designed, and the solubility and electrochromic properties of the polyamide were improved by utilizing the steric hindrance of triphenylamine and the electron affinity of quinoxaline.
It significantly improves the solubility and film-forming properties of polyamides, improves electrochromic properties, including optical contrast and cyclic stability. The number of cycles increased from 20 to 1500 times to 2200 times, and the optical contrast increased from about 40% to 80%.
Smart Images

Figure CN119552352A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a triphenylamine polyamide containing a quinoxaline structure, namely a polyamide based on 2,3-bis[4-aminophenyl(4-methoxyphenyl)amino]quinoxaline and a commercially available dicarboxylic acid, and a preparation method and application thereof. Background Art
[0002] Triphenylamine is a class of organic compounds with a propeller structure centered on nitrogen atoms, which has strong electron-donating ability and good hole transport properties. Among them, triphenylamine derivatives can undergo reversible redox reactions under an external electric field and are accompanied by rich color changes, making them an important class of electrochromic materials. At the same time, due to their high electron affinity, quinoxaline and its derivatives can be used as electron acceptors to form DA structural elements with triphenylamine to reduce the band gap, shift the absorption spectrum of the compound to the right, and make the electrochromic response more sensitive and stable. Further, based on this molecule and commercial dicarboxylic acids, a series of polyamide materials with good solution processability were prepared, and finally high-performance electrochromic devices were prepared. This patent introduces the above-mentioned DA building block into the polyamide structure. Compared with other reported triarylamine polymers containing quinoxaline structures, such as poly (6,9-bis(4-(diphenylamino)phenyl)-1,2,3,4-tetrahydrophenazine) [Chinese Journal of Organic Chemistry, 2020, 40(08):2513-2519], poly (N 1 ,N 1 '-(Dibenzo[a,c]phenazine-10,13-diyl)bis(N 1 -(4-methoxyphenyl)benzene-1,4-diamine) [European Polymer Journal, 2024, 211: 113012] and poly 4,4'-(dibenzo[a,c]phenazine-10,13-diyl)bis(N,N-diphenylaniline [New Chemistry Journal 2021, 45(40): 19082-19087], etc. The polyamide in the present invention has a better comprehensive performance in electrochromism, and its optical contrast is increased from about 40% to 80%, and the number of cycles is increased from 20 to 1500 times to 2200 times, and the color change response is sensitive (1.5 to 2.9s). Summary of the invention
[0003] The purpose of the present invention is to solve the problems of polyamide, such as difficulty in solution processing, poor film-forming effect and poor electrochromic cycle stability, and proposes a triphenylamine polyamide containing a quinoxaline structure, a preparation method thereof and an application in electrochromism. 2,3-bis[4-aminophenyl(4-methoxyphenyl)amino]quinoxaline is respectively polycondensed with commercially available diacid monomers (including but not limited to 1,4-cyclohexanedicarboxylic acid, 4,4'-diphenyl ether dicarboxylic acid, 4,4'-dicarboxy biphenyl sulfone, 2,2-bis(4-carboxyphenyl)hexafluoropropane, 4,4'-biphenyl dicarboxylic acid, 1,4-naphthalene dicarboxylic acid, 2,7-naphthalene dicarboxylic acid, terephthalic acid, isophthalic acid, 3,4-thiophene dicarboxylic acid, 3,4-furan dicarboxylic acid, succinic acid, etc.) to obtain a triphenylamine polyamide, and its general structural formula is as follows: In the formula, n is an integer of 3 to 26, and the three polyamides obtained by polycondensation of diacid monomers (1,4-cyclohexanedicarboxylic acid, 4,4'-diphenyl ether dicarboxylic acid and 4,4'-dicarboxybiphenyl sulfone) are named P1, P2 and P3 respectively. 2. The method for preparing the triphenylamine-based polyamide containing quinoxaline structure of the present invention is carried out according to the following steps: 1. Synthesis of 2,3-bis[4-aminophenyl(4-methoxyphenyl)amino]quinoxaline monomer ① Under nitrogen atmosphere, add 1,2-bis(4-bromophenyl)ethane-1,2-dione to a three-necked bottle containing glacial acetic acid, heat and stir at 80°C to completely dissolve it, and then add o-phenylenediamine to the above reaction solution. After reacting for 12 hours, cool the reaction solution to room temperature, let it stand to precipitate, filter to obtain a white needle-shaped crystalline product, and vacuum dry the product to obtain 2,3-bis(4-bromophenyl)quinoxaline, named M1. The ratio of the volume of glacial acetic acid to the amount of 1,2-bis(4-bromophenyl)ethane-1,2-dione in step 1① is 15 mL:1.2 mmol; The molar ratio of 1,2-bis(4-bromophenyl)ethane-1,2-dione to o-phenylenediamine in step 1① is 1:1; ② Under nitrogen atmosphere, add 4-methoxy-N-(4-nitrophenyl)aniline, M1, 18-crown ether-6, copper powder, potassium carbonate and o-dichlorobenzene into a three-necked flask, heat to 180°C, and condense and reflux for 36 hours. After the reaction is completed, filter while hot, pour the filtrate into petroleum ether and stir continuously until a yellow precipitate is precipitated, filter the precipitate, and then purify the yellow precipitate by column chromatography, collect the target product and remove the solvent by rotary evaporator, and finally vacuum dry the purified product to obtain a yellow powdery monomer product 2,3-di[4-nitrophenyl(4-methoxyphenyl)amino]quinoxaline, named M2. The molar ratio of M1 to 4-methoxy-N-(4-nitrophenyl)aniline in step 1② is 1:2.5; The molar ratio of M1 to 18-crown-6 in step 1② is 1:1; The molar ratio of M1 to copper powder in step 1② is 1:8; The molar ratio of the copper powder to potassium carbonate in step 1② is 1:1; ③ Under nitrogen atmosphere, add M2, anhydrous ethanol, and Pd / C into a three-necked flask, gradually heat to 80°C, and use a constant pressure dropping funnel to add hydrazine hydrate dropwise to the above reaction solution. After the reaction is carried out for 12 hours, remove the heating device and filter while hot to remove palladium carbon. Subsequently, pour the filtrate into saturated brine and stir continuously until a large amount of solid precipitates. Filter the solid and wash it thoroughly with ethanol, and then vacuum dry to obtain an orange powdery monomer product 2,3-di[4-aminophenyl(4-methoxyphenyl)amino]quinoxaline, named M3. The ratio of the volume of anhydrous ethanol to the amount of substance of M2 in step 1③ is (80-100) mL:1.3 mmol; The ratio of the mass of Pd / C to the amount of substance of M2 in step 1③ is (0.3-0.5) g:1.3 mmol; 2. Preparation of triphenylamine polyamide containing quinoxaline structure: 2,3-bis[4-aminophenyl(4-methoxyphenyl)amino]quinoxaline (M3), diacid monomer, triphenyl phosphite, anhydrous calcium chloride, pyridine and N-methylpyrrolidone were added to a three-necked flask and stirred for 8 hours under heating conditions at 130°C. After the polymerization reaction was completed, the reaction solution was cooled to room temperature and poured into methanol to generate a precipitate, which was collected by filtration and washed with methanol, and finally Soxhlet extraction was performed with acetone to obtain a triphenylamine polyamide containing a quinoxaline structure. In step 2, the ratio of the amount of M3 to the diacid monomer is 1:1; The ratio of the mass of calcium chloride to the volume of N-methylpyrrolidone in step 2 is 0.15 g:1.5 mL; The ratio of the volume of N-methylpyrrolidone in step 2 to the amount of M3 substance is 3 mL: 1 mmol; The ratio of the volume of triphenyl phosphite in step 2 to the amount of substance of M3 is 1.1 mL: 1 mmol; The ratio of the volume of pyridine in step 2 to the amount of substance of M3 is 0.6 mL: 1 mmol; The triphenylamine polyamide containing a quinoxaline structure of the present invention is used as an electrochromic material in display, camouflage, smart windows and other electrochromic related fields. The present invention is to prepare a polyamide material with long-lasting electrochemical cycle stability and excellent comprehensive electrochromic ability, improve the problems of polyamide being difficult to process in solution, poor film-forming effect and poor electrochromic cycle stability, and introduce a triphenylamine motif with a propeller structure and a nitrogen-containing quinoxaline condensed ring motif into the polymer by design, on the one hand, the large steric hindrance of triphenylamine and its methoxy substituent can increase the solubility of the polyamide, and facilitate solution coating processing; on the other hand, the triphenylamine motif provides the polymer with a nitrogen atom as an active center of the redox electrochemical reaction, so that it has electrochromic performance, and at the same time, due to the introduction of a methoxy group at the end, the stability of the free radical generated after electrochemical oxidation is increased, thereby improving the electrochromic cycle stability. In particular, quinoxaline and its derivatives can be used as electron acceptors to form a DA structure with triphenylamine due to their high electron affinity, thereby reducing the band gap and making the electrochromic response more sensitive and stable, and at the same time, the quinoxaline derivatives also have unique photophysical properties, and their fluorescence properties can be used for detection. Combining the above advantages, the triphenylamine polyamide containing a quinoxaline structure prepared by the present invention has good solubility and film-forming properties, shows excellent performance of high contrast and long-term cycle stability in electrochromism, and uses fluorescence properties to detect the explosive 2,4,6-trinitrophenol. A triarylamine-based polyamide containing a quinoxaline structure, a preparation method thereof, and electrochromic and fluorescence detection applications are provided. The present invention has the following beneficial effects: 1. The polyamide containing quinoxaline and triphenylamine structures of the present invention increases the solubility of the polyamide due to the modification of methoxy groups at the para-position of the benzene ring of triphenylamine. The polyamide is easily soluble in polar solvents, and 0.2 to 0.3 grams can be dissolved in each milliliter of polar solvent. The thermal weight loss curve of the polyamide is measured in air to evaluate its thermal stability. The polyamide containing quinoxaline and triphenylamine structures begins to lose a small amount of weight at 300° C. When the temperature is 360 to 450° C., the residual carbon residue is 95%; when the temperature reaches 800° C., the residual carbon residue is 35 to 47%. The above results show that the polyamide has good solubility and thermal stability. 2. The polymer of the present invention has excellent electrochromic properties Electrochromism refers to the phenomenon that a material undergoes an oxidation-reduction reaction under the action of an external electric field and exhibits a color change. The triphenylamine polyamide containing a quinoxaline structure of the present invention has a significant electrochromic phenomenon. The combination of the quinoxaline structure and the triphenylamine unit promotes the electron transfer between the two, thereby making the color change of the polymer after oxidation more obvious. When a voltage of 1.0V is applied, the coloring time of the polyamide of the present invention is 2.1 to 2.9s; the bleaching time is 0.9 to 1.5s; it is dark green when colored and light yellow when bleached. Compared with existing polymers containing quinoxaline structures such as poly (4,4'-(dibenzo[a,c]phenazine-10,13-diyl)bis(N,N-diphenylaniline) [New Chemistry Journal, 2021, 45(40):19082-19087], it shows a higher optical contrast, which increases from about 40% to 80%. At the same time, it has excellent long-term cycle stability, and the number of cycles increases from 500 to 2200 times, showing excellent electrochromic stability. 3. The polymer P1 of the present invention has a strong fluorescence. After the polymer of the present invention is in contact with a solution prepared from the explosive 2,4,6-trinitrophenol TNP, the fluorescence of the polymer gradually decreases until it disappears. Therefore, the polymer of the present invention can be used to detect the explosive TNP. BRIEF DESCRIPTION OF THE DRAWINGS
[0004] Figure 1 This is the H NMR spectrum of the 2,3-bis[4-aminophenyl(4-methoxyphenyl)amino]quinoxaline monomer prepared in Example 1; Figure 2 The infrared spectra of the triphenylamine polyamide containing quinoxaline structure prepared in Examples 1 to 3; Figure 3 The cyclic voltammograms of the triphenylamine polyamide containing quinoxaline structure prepared in Examples 1 to 3; Figure 4 The thermal gravimetric loss curves of the triphenylamine polyamide containing quinoxaline structure prepared in Examples 1 to 3; Figure 5 This is the UV-visible-near infrared absorption graph of the triphenylamine polyamide containing quinoxaline structure prepared in Example 1; Figure 6 This is a graph of the electrochromic cycle stability of the triphenylamine polyamide containing a quinoxaline structure prepared in Example 1; Figure 7 This is a graph showing the electrochromic response time of the triphenylamine polyamide containing a quinoxaline structure prepared in Example 1; Figure 8 This is a fluorescence image of the triphenylamine polyamide containing quinoxaline structure prepared in Example 1 in response to TNP; DETAILED DESCRIPTION
[0005] The technical solution of the present invention is not limited to the specific implementation modes listed below, but also includes reasonable combinations of various specific implementation modes. Specific embodiment 1: The general structure formula of the triphenylamine polyamide containing quinoxaline structure in this embodiment is as follows: In the formula, n is an integer from 3 to 26. This implementation has the following beneficial effects: 1. The polyamide containing quinoxaline and triphenylamine structures of the present invention has increased solubility of the polyamide due to the introduction of methoxy groups, and is easily soluble in polar solvents, with 0.2 to 0.3 grams being dissolveable per milliliter of polar solvent. The thermal weight loss curve of the polyamide is measured in air to evaluate its thermal stability. The polyamide containing quinoxaline and triphenylamine structures begins to lose weight slightly at 300° C. When the temperature is 360 to 450° C., the residual carbon content is 95%; when the temperature reaches 800° C., the residual carbon content is 35 to 47%. The above results indicate that the polyamide has good solubility and thermal stability. 2. The polymer of the present invention has excellent electrochromic properties and can be applied to electrochromic related fields. Electrochromism refers to the phenomenon that a material undergoes an oxidation-reduction reaction under the action of an external electric field and exhibits a color change. The triphenylamine polyamide containing a quinoxaline structure of the present invention has an obvious electrochromic phenomenon. The combination of the quinoxaline structure and the triphenylamine unit promotes the electron transfer between the two, making the color change of the polymer after oxidation more obvious. When a voltage of 1.0V is applied, the coloring time of the polyamide of the present invention is 2.1 to 2.9s; the bleaching time is 0.9 to 1.5s; it is dark green when colored and light yellow when bleached, and the electrochromic contrast is high, wherein the optical contrast of polymer P1 can reach up to 80%. The triphenylamine-based polyamide containing a quinoxaline structure prepared by the present invention has good electrochemical redox cycle stability. After 1200 cycles, the optical contrast of polymer P1 does not change significantly. When the number of cycles reaches 2200, the optical contrast of the film still retains 80%, showing excellent electrochromic stability. 3. The polymer P1 of the present invention has a strong fluorescence. After the polymer of the present invention is in contact with a solution prepared from the explosive 2,4,6-trinitrophenol TNP, the fluorescence of the polymer gradually decreases until it disappears. Therefore, the polymer of the present invention can be used to detect TNP. Specific embodiment 2: The preparation method of triphenylamine-based polyamide containing quinoxaline structure in this embodiment is carried out according to the following steps: 1. Synthesis of 2,3-bis[4-aminophenyl(4-methoxyphenyl)amino]quinoxaline monomer ① Under nitrogen atmosphere, add 1,2-bis(4-bromophenyl)ethane-1,2-dione to a three-necked bottle containing glacial acetic acid, heat and stir at 80°C to completely dissolve it, and then add o-phenylenediamine to the above reaction solution. After reacting for 12 hours, cool the reaction solution to room temperature, let it stand to precipitate, filter to obtain a white needle-shaped crystalline product, and vacuum dry the product to obtain 2,3-bis(4-bromophenyl)quinoxaline, named M1. The ratio of the volume of glacial acetic acid to the amount of 1,2-bis(4-bromophenyl)ethane-1,2-dione in step 1① is 15 mL:1.2 mmol; The molar ratio of 1,2-bis(4-bromophenyl)ethane-1,2-dione to o-phenylenediamine in step 1① is 1:1; ② Under nitrogen atmosphere, add 4-methoxy-N-(4-nitrophenyl)aniline, M1, 18-crown ether-6, copper powder, potassium carbonate and o-dichlorobenzene into a three-necked flask, heat to 180°C, and condense and reflux for 36 hours. After the reaction is completed, filter while hot, pour the filtrate into petroleum ether and stir continuously until a yellow precipitate is precipitated, filter the precipitate, and then purify the yellow precipitate by column chromatography, collect the target product and remove the solvent by rotary evaporator, and finally vacuum dry the purified product to obtain a yellow powdery monomer product 2,3-di[4-nitrophenyl(4-methoxyphenyl)amino]quinoxaline, named M2. The molar ratio of M1 to 4-methoxy-N-(4-nitrophenyl)aniline in step 1② is 1:2.5; The molar ratio of M1 to 18-crown-6 in step 1② is 1:1; The molar ratio of M1 to copper powder in step 1② is 1:8; The molar ratio of the copper powder to potassium carbonate in step 1② is 1:1; ③ Under nitrogen atmosphere, add M2, anhydrous ethanol, and Pd / C into a three-necked flask, gradually heat to 80°C, and use a constant pressure dropping funnel to add hydrazine hydrate dropwise to the above reaction solution. After the reaction is carried out for 12 hours, remove the heating device and filter while hot to remove palladium carbon. Subsequently, pour the filtrate into saturated brine and stir continuously until a large amount of solid precipitates. Filter the solid and wash it thoroughly with ethanol, and then vacuum dry to obtain an orange powdery monomer product 2,3-di[4-aminophenyl(4-methoxyphenyl)amino]quinoxaline, named M3. The ratio of the volume of anhydrous ethanol to the amount of substance of M2 in step 1③ is (80-100) mL:1.3 mmol; The ratio of the mass of Pd / C to the amount of substance of M2 in step 1③ is (0.3-0.5) g:1.3 mmol; 2. Preparation of triphenylamine polyamide containing quinoxaline structure: 2,3-bis[4-aminophenyl(4-methoxyphenyl)amino]quinoxaline (M3), diacid monomer, triphenyl phosphite, anhydrous calcium chloride, pyridine and N-methylpyrrolidone were added to a three-necked flask and stirred for 8 hours under heating conditions at 130°C. After the polymerization reaction was completed, the reaction solution was cooled to room temperature and poured into methanol to generate a precipitate, which was collected by filtration and washed with methanol, and finally Soxhlet extraction was performed with acetone to obtain a triphenylamine polyamide containing a quinoxaline structure. In step 2, the ratio of the amount of M3 to the diacid monomer is 1:1; The ratio of the mass of calcium chloride to the volume of N-methylpyrrolidone in step 2 is 0.15 g:1.5 mL; The ratio of the volume of N-methylpyrrolidone in step 2 to the amount of M3 substance is 3 mL: 1 mmol; The ratio of the volume of triphenyl phosphite in step 2 to the amount of substance of M3 is 1.1 mL: 1 mmol; The ratio of the volume of pyridine in step 2 to the amount of substance of M3 is 0.6 mL: 1 mmol; Specific implementation method three: In this implementation method, triphenylamine-based polyamide containing quinoxaline structure is used as an electrochromic layer in an electrochromic device. Specific embodiment 4: This embodiment is different from specific embodiment 3 in that the application of triphenylamine-based polyamide containing quinoxaline structure as an electrochromic layer in an electrochromic device is carried out according to the following steps: triphenylamine-based polyamide containing quinoxaline structure is used as an electrochromic layer in an electrochromic device, its solution is coated on the surface of the conductive film of a conductive substrate, another conductive glass is used as a counter electrode, an acetonitrile solution of lithium perchlorate / tetrabutylammonium perchlorate with a concentration of 0.1M or a gel electrolyte containing PMMA is injected between the color-changing electrode and the counter electrode, and an electrochromic device is prepared. Others are the same as specific embodiment 3. Specific embodiment 5: This embodiment is different from specific embodiment 3 or 4 in that the conductive substrate is ITO conductive glass or polyester film with ITO sputtered on the surface or transparent glass or polyester film with nano silver wires on the surface. Other steps and parameters are the same as those of specific embodiment 3 or 4. Specific implementation method 6: This implementation method is different from specific implementation methods 3 to 5 in that the voltage of the external electric field is 0.0 V to 2.6 V. The other steps and parameters are the same as those of specific implementation methods 3 to 5. The following examples are used to verify the beneficial effects of the present invention: Example 1: The structural formula of the triphenylamine polyamide P1 containing a quinoxaline structure is as follows: , where n is 3 to 26. 1. Synthesis of 2,3-bis[4-aminophenyl(4-methoxyphenyl)amino]quinoxaline monomer ① Under nitrogen atmosphere, add 1,2-bis(4-bromophenyl)ethane-1,2-dione to a three-necked bottle containing glacial acetic acid, heat and stir at 80°C to completely dissolve it, and then add o-phenylenediamine to the above reaction solution. After reacting for 12 hours, cool the reaction solution to room temperature, let it stand to precipitate, filter to obtain a white needle-shaped crystalline product, and vacuum dry the product to obtain 2,3-bis(4-bromophenyl)quinoxaline, named M1. The ratio of the volume of glacial acetic acid to the amount of 1,2-bis(4-bromophenyl)ethane-1,2-dione in step 1① is 15 mL:1.2 mmol; The molar ratio of 1,2-bis(4-bromophenyl)ethane-1,2-dione to o-phenylenediamine in step 1① is 1:1; ② Under nitrogen atmosphere, add 4-methoxy-N-(4-nitrophenyl)aniline, M1, 18-crown ether-6, copper powder, potassium carbonate and o-dichlorobenzene into a three-necked flask, heat to 180°C, and condense and reflux for 36 hours. After the reaction is completed, filter while hot, pour the filtrate into petroleum ether and stir continuously until a yellow precipitate is precipitated, filter the precipitate, and then purify the yellow precipitate by column chromatography, collect the target product and remove the solvent by rotary evaporator, and finally vacuum dry the purified product to obtain a yellow powdery monomer product 2,3-di[4-nitrophenyl(4-methoxyphenyl)amino]quinoxaline, named M2. The molar ratio of M1 to 4-methoxy-N-(4-nitrophenyl)aniline in step 1② is 1:2.5; The molar ratio of M1 to 18-crown-6 in step 1② is 1:1; The molar ratio of M1 to copper powder in step 1② is 1:8; The molar ratio of the copper powder to potassium carbonate in step 1② is 1:1; ③ Under nitrogen atmosphere, add M2, anhydrous ethanol, and Pd / C into a three-necked flask, gradually heat to 80°C, and use a constant pressure dropping funnel to add hydrazine hydrate dropwise to the above reaction solution. After the reaction is carried out for 12 hours, remove the heating device and filter while hot to remove palladium carbon. Subsequently, pour the filtrate into saturated brine and stir continuously until a large amount of solid precipitates. Filter the solid and wash it thoroughly with ethanol, and then vacuum dry to obtain an orange powdery monomer product 2,3-di[4-aminophenyl(4-methoxyphenyl)amino]quinoxaline, named M3. The ratio of the volume of anhydrous ethanol to the amount of substance of M2 in step 1③ is (80-100) mL:1.3 mmol; The ratio of the mass of Pd / C to the amount of substance of M2 in step 1③ is (0.3-0.5) g:1.3 mmol; 2. Preparation of triphenylamine polyamide containing quinoxaline structure: 2,3-bis[4-aminophenyl(4-methoxyphenyl)amino]quinoxaline (M3), diacid monomer, triphenyl phosphite, anhydrous calcium chloride, pyridine and N-methylpyrrolidone were added to a three-necked flask and stirred for 8 hours under heating conditions at 130°C. After the polymerization reaction was completed, the reaction solution was cooled to room temperature and poured into methanol to generate a precipitate, which was collected by filtration and washed with methanol, and finally Soxhlet extraction was performed with acetone to obtain a triphenylamine polyamide containing a quinoxaline structure. In step 2, the ratio of the amount of M3 to the diacid monomer is 1:1; The ratio of the mass of calcium chloride to the volume of N-methylpyrrolidone in step 2 is 0.15 g:1.5 mL; The ratio of the volume of N-methylpyrrolidone in step 2 to the amount of M3 substance is 3 mL: 1 mmol; The ratio of the volume of triphenyl phosphite in step 2 to the amount of substance of M3 is 1.1 mL: 1 mmol; The ratio of the volume of pyridine in step 2 to the amount of substance of M3 is 0.6 mL: 1 mmol; Embodiment 2 to Embodiment 3: The structures of triphenylamine polyamides P2 and P3 containing quinoxaline structure are similar to that of P1. The specific preparation method of P2 is the same as that of Example 1 P1, except that in Example 2, 4,4'-diphenyl ether dicarboxylic acid is used instead of 1,4-cyclohexanedicarboxylic acid. The specific preparation method of P3 is the same as that of Example 1 P1, except that in Example 3, 4,4'-dicarboxybiphenyl sulfone is used instead of 1,4-cyclohexanedicarboxylic acid. Figure 1 This is the hydrogen nuclear magnetic spectrum of the 2,3-bis[4-aminophenyl(4-methoxyphenyl)amino]quinoxaline monomer prepared in Example 1; Figure 2 is the infrared spectrum of the triphenylamine polyamide containing quinoxaline structure prepared in Examples 1 to 3; Figure 2 It can be seen that Figure 2 Medium 3310~3360cm -1 The characteristic absorption peak of -NH- in the amide bond, 1675 cm -1 is the characteristic absorption peak of the carbonyl group in the amide bond, 1240 cm -1is the characteristic absorption peak of NC in the amide bond. In addition, the fingerprint region of the infrared spectra of polymers P1-P3 shows a peak at 754 cm -1 and 826cm -1 Two characteristic vibration peaks of ortho / para disubstituted benzene rings. It is explained that Examples 1 to 3 synthesized triphenylamine polyamides containing quinoxaline structures; Figure 3 The cyclic voltammograms of the triphenylamine polyamide containing quinoxaline structure prepared in Examples 1 to 3; Figure 3 It can be seen that the polymer P1 has an oxidation peak at about 0.97V, and the reduction peak appears at 0.53V; the polymer P2 has an oxidation peak at 0.92V, and its reduction peak appears at 0.66V; the polymer P3 has an oxidation peak at 1.03V, and its reduction peak appears at 0.56V; this indicates that the triphenylamine polyamide containing a quinoxaline structure prepared in Examples 1 to 3 undergoes an electrochemical redox reaction under the condition of applying an external voltage, and the triphenylamine polyamide containing a quinoxaline structure will show a color change during the redox process; this indicates that the triphenylamine polyamide containing a quinoxaline structure prepared in Examples 1 to 3 has an electrochromic property; Figure 4 The thermal weight loss curves of the triphenylamine polyamide containing quinoxaline structure prepared in Examples 1 to 3; Figure 4 It can be seen that the thermal decomposition temperature range of the three polyamides prepared in Examples 1 to 3 when the weight loss in air is 10% is 426-513°C, indicating that they have good thermal stability. When the heating temperature is increased to 800°C, the residual carbon rate of the polymers is greater than 35%, among which the residual carbon rate of polymers P2 and P3 is greater than 45%, which is due to the triphenylamine and quinoxaline moieties in the polymer structure having high content of aromatic and condensed ring structures. It can be shown that this series of polymers have good thermal stability and are expected to be used in high temperature working environments. Figure 5 This is the electrochromic diagram of the triphenylamine polyamide containing quinoxaline structure prepared in Example 1; the electrochromic properties of the polyamide are determined by testing the changes in absorbance / transmittance in its ultraviolet-visible-near-infrared absorption spectrum as the applied potential increases. Taking the electrochromic properties of P1 as an example, as the applied potential increases, the intensity of the absorption peak at 315nm gradually decreases, while the intensity of the absorption peaks at 385nm and 795nm increases sharply, and the color of the polyamide film changes from light yellow to light green. When the applied voltage increases to 0.8V, the absorption value of the P1 film in the long wavelength range shows a significant increase. When the applied voltage continues to increase to 1.3V, the absorption value of P1 reaches the maximum, and the color of the film changes to dark green. Figure 6 The dynamic curve of the transmittance of the P1 film changing with time under the conditions of 0.0V to 0.9V voltage and 795nm monitoring wavelength; Figure 6 It can be seen that the optical contrast of P1 is 80%. After 1200 cycles, its optical contrast has basically not changed significantly, indicating that polymer P1 has excellent electrochromic stability. Figure 7 This is a complete redox process of the P1 film in the color change stabilization stage during the step test. After calculation, the coloring time of the P1 film is 2.9s and the fading time is 1.5s, indicating that it has excellent electrochromic response speed. Figure 8 The fluorescence image of the triphenylamine polyamide containing quinoxaline structure prepared in Example 1 in response to 2,4,6-trinitrophenol TNP; 1 mg of polymer P1 was dissolved in 20 mL of tetrahydrofuran solution to obtain a concentration of 1×10 -5 M polymer solution, gradually add 1 μM TNP solution to the polymer solution. Figure 8 It can be seen that with the increase of TNP concentration, the fluorescence of the polymer solution gradually weakened. The quenching constant K was calculated according to the Stern-Volmer equation. SV 3.12×10 4 M -1 , and then according to the formula L OD =3S / K SV The detection limit of P1 was found to be 2.02 μM, which indicates that the polymer can respond to TNP and the presence of TNP can be determined by whether the fluorescence of the polymer solution decreases.
Claims
1. A diamine monomer containing quinoxaline and triphenylamine structural units, i.e., 2,3-bis[4-aminophenyl(4-methoxyphenyl)amino]quinoxaline, is respectively polycondensed with commercially available diacid monomers (including but not limited to 1,4-cyclohexanedicarboxylic acid, 4,4'-diphenyl ether dicarboxylic acid, 4,4'-dicarboxybiphenyl sulfone, 2,2-bis(4-carboxyphenyl)hexafluoropropane, 4,4'-biphenyl dicarboxylic acid, 1,4-naphthalene dicarboxylic acid, 2,7-naphthalene dicarboxylic acid, terephthalic acid, isophthalic acid, 3,4-thiophene dicarboxylic acid, 3,4-furan dicarboxylic acid, succinic acid, etc.) to obtain a polyamide, the general structural formula of which is as follows: In the formula, n is an integer from 3 to 26.
2. The polyamide preparation method based on 2,3-bis[4-aminophenyl(4-methoxyphenyl)amino]quinoxaline and commercially available dicarboxylic acid of the present invention is carried out according to the following steps:
1. Synthesis of 2,3-bis[4-aminophenyl(4-methoxyphenyl)amino]quinoxaline monomer ① Under nitrogen atmosphere, add 1,2-bis(4-bromophenyl)ethane-1,2-dione to a three-necked bottle containing glacial acetic acid, heat and stir at 80°C to completely dissolve it, and then add o-phenylenediamine to the above reaction solution. After reacting for 12 hours, cool the reaction solution to room temperature, let it stand to precipitate, filter to obtain a white needle-shaped crystalline product, and vacuum dry the product to obtain 2,3-bis(4-bromophenyl)quinoxaline, named M1. The ratio of the volume of glacial acetic acid to the amount of 1,2-bis(4-bromophenyl)ethane-1,2-dione in step 1① is 15 mL:1.2 mmol; The molar ratio of 1,2-bis(4-bromophenyl)ethane-1,2-dione to o-phenylenediamine in step 1① is 1:1; ② Under nitrogen atmosphere, add 4-methoxy-N-(4-nitrophenyl)aniline, M1, 18-crown ether-6, copper powder, potassium carbonate and o-dichlorobenzene into a three-necked flask, heat to 180°C, and condense and reflux for 36 hours. After the reaction is completed, filter while hot, pour the filtrate into petroleum ether and stir continuously until a yellow precipitate is precipitated, filter the precipitate, and then purify the yellow precipitate by column chromatography, collect the target product and remove the solvent by rotary evaporator, and finally vacuum dry the purified product to obtain a yellow powdery monomer product 2,3-di[4-nitrophenyl(4-methoxyphenyl)amino]quinoxaline, named M2. The molar ratio of M1 to 4-methoxy-N-(4-nitrophenyl)aniline in step 1② is 1:2.5; The molar ratio of M1 to 18-crown-6 in step 1② is 1:1; The molar ratio of M1 to copper powder in step 1② is 1:8; The molar ratio of the copper powder to potassium carbonate in step 1② is 1:1; ③ Under nitrogen atmosphere, add M2, anhydrous ethanol, and Pd / C into a three-necked flask, gradually heat to 80°C, and use a constant pressure dropping funnel to add hydrazine hydrate dropwise to the above reaction solution. After the reaction is carried out for 12 hours, remove the heating device and filter while hot to remove palladium carbon. Subsequently, pour the filtrate into saturated brine and stir continuously until a large amount of solid precipitates. Filter the solid and wash it thoroughly with ethanol, and then vacuum dry to obtain an orange powdery monomer product 2,3-di[4-aminophenyl(4-methoxyphenyl)amino]quinoxaline, named M3. The ratio of the volume of anhydrous ethanol to the amount of substance of M2 in step 1③ is (80-100) mL:1.3 mmol; The ratio of the mass of Pd / C to the amount of substance of M2 in step 1③ is (0.3-0.5) g:1.3 mmol; 2. Preparation of triphenylamine polyamide containing quinoxaline structure: 2,3-bis[4-aminophenyl(4-methoxyphenyl)amino]quinoxaline (M3), diacid monomer, triphenyl phosphite, anhydrous calcium chloride, pyridine and N-methylpyrrolidone were added to a three-necked flask and stirred for 8 hours under heating conditions at 130°C. After the polymerization reaction was completed, the reaction solution was cooled to room temperature and poured into methanol to generate a precipitate, which was collected by filtration and washed with methanol, and finally Soxhlet extraction was performed with acetone to obtain a triphenylamine polyamide containing a quinoxaline structure. In step 2, the ratio of the amount of M3 to the diacid monomer is 1:1; The ratio of the mass of calcium chloride to the volume of N-methylpyrrolidone in step 2 is 0.15 g:1.5 mL; The ratio of the volume of N-methylpyrrolidone in step 2 to the amount of M3 substance is 3 mL: 1 mmol; The ratio of the volume of triphenyl phosphite in step 2 to the amount of substance of M3 is 1.1 mL: 1 mmol; The ratio of the volume of pyridine in step 2 to the amount of substance of M3 is 0.6 mL:1 mmol.
3. The method for preparing the triphenylamine-based polyamide containing quinoxaline structure according to claim 2, characterized in that: The ratio of the volume of the o-dichlorobenzene solution in step 1② to the amount of substance of M1 is 20mL:2.3mmol.
4. The method for preparing a triphenylamine polymer containing a quinoxaline structure according to claim 2, characterized in that: The dicarboxylic acid monomers described in step 2 are 1,4-cyclohexanedicarboxylic acid, 4,4'-diphenyl ether dicarboxylic acid and 4,4'-dicarboxybiphenyl sulfone, but are not limited to these three diacid monomers. The prepared polyamides are P1, P2, P3 and other corresponding polyamides.
5. Use of the triphenylamine-based polymer containing a quinoxaline structure according to claim 1 as an electrochromic active layer in an electrochromic device in electrochromic aspects.
6. The use according to claim 5, characterized in that: The application of the triphenylamine-based polymer containing a quinoxaline structure as the electrochromic layer of an electrochromic device is carried out according to the following steps: A triphenylamine-based polymer solution containing a quinoxaline structure is coated on the conductive film surface of a transparent conductive substrate, another conductive transparent electrode is used as a counter electrode, and an acetonitrile solution of 0.1M lithium perchlorate / tetrabutylammonium perchlorate or a gel electrolyte containing PMMA is injected between the color-changing electrode and the counter electrode to prepare an electrochromic device.
7. The use according to claim 5, characterized in that: The conductive substrate is ITO conductive glass or a polyester film with ITO sputtered on the surface or a transparent glass or polyester film with nano silver wires on the surface.
8. The use according to claim 5, characterized in that: The voltage of the externally applied electric field is 0.0V to 2.6V. The present invention is to prepare a polyamide material with long-lasting electrochemical cycle stability and excellent comprehensive electrochromic ability, improve the problems of polyamide being difficult to process in solution, poor film-forming effect and poor electrochromic cycle stability, and introduce a triphenylamine motif with a propeller structure and a nitrogen-containing quinoxaline condensed ring motif into the polymer by design, on the one hand, the large steric hindrance of triphenylamine and its methoxy substituent can increase the solubility of the polyamide, and facilitate solution coating processing; on the other hand, the triphenylamine motif provides the polymer with a nitrogen atom as an active center of the redox electrochemical reaction, so that it has electrochromic performance, and at the same time, due to the introduction of a methoxy group at the end, the stability of the free radical generated after electrochemical oxidation is increased, thereby improving the electrochromic cycle stability. In particular, quinoxaline and its derivatives can be used as electron acceptors to form a DA structure with triphenylamine due to their high electron affinity, thereby reducing the band gap and making the electrochromic response more sensitive and stable, and at the same time, the quinoxaline derivatives also have unique photophysical properties, and their fluorescence properties can be used for detection. Combining the above advantages, the triphenylamine polyamide containing quinoxaline structure prepared by the present invention has good solubility and film-forming properties, and has good electrochromic properties compared with the existing poly 6,9-bis(4-(diphenylamino)phenyl)-1,2,3,4-tetrahydrophenazine [Chinese Journal of Organic Chemistry, 2020, 40(08):2513-2519], poly N 1 ,N 1 '-(Dibenzo[a,c]phenazine-10,13-diyl)bis(N 1 -(4-methoxyphenyl)benzene-1,4-diamine)[European Polymer Journal, 2024, 211:113012] Compared with polymers containing quinoxaline structures, it shows a higher optical contrast, which increases from about 40% to 80%, and has excellent long-cycle stability. The number of cycles increases from 500 to 1500 times to 2200 times; the fluorescence performance is used to detect the explosive 2,4,6-trinitrophenol TNP. Under the action of TNP, the fluorescence gradually disappears, and a polyamide synthesized from 2,3-bis[4-aminophenyl(4-methoxyphenyl)amino]quinoxaline, a preparation method and application thereof are provided.